Effects of Ulnar Styloid Fractures on Unstable Distal Radius Fracture Outcomes: A Systematic Review of Comparative Studies - Almedghio, Sami; Arshad, Mohammed Shoaib; Almari, Fayez; Chakrabarti, Indranil (Journal of Wrist Surgery, 2018)
Purpose In this literature review, functional outcomes such as Disability of Arm, Shoulder and Hand (DASH) score and the visual analog scale (VAS) of pain along with clinical outcomes such as range of movement and grip strength of treated distal radius fractures (DRF) accompanied with ulnar styloid fractures (USF) will be compared with those with isolated DRF.Materials and Methods We analyzed articles from MEDLINE, Embase, and CINAHL that met our predetermined inclusion and exclusion criteria as per the Preferred Reporting Items for Systematic Reviews and Meta-analysis statements. This resulted in the identification of 464 articles with 18 potentially eligible studies of which 6 were included at the full-text screening stage. The primary outcomes were wrist pain, range of motion, functional outcome and satisfaction, such as VAS, and the DASH questionnaire along with radiological assessment and incidence of complications.Results These studies involved 796 participants with DRF and 806 wrists with DRF; 444 (55%) of DRF had an associated USF. Three studies did not report any statistically significant difference in DASH scores between the DRF patients with or without USF. Two studies reported worse DASH scores in the group with associated USF. Wrist pain was reported to be statistically significantly worse in patients with associated USF in two studies. Grip strength did not exhibit a statistically significant difference in any groups in four studies. On assessing the range of motion of the wrist and forearm, only one study reported a statistically significant difference in flexion at 2 years follow-up, with less flexion in patients with USF.Conclusion This review suggests that there is no significant correlation between a USF and the functional and clinical outcomes of DRF treatment, albeit wrist pain and less flexion were reported in some studies to be associated with USF. There is a need for more robust evidence from large randomized controlled trials to specifically look at the effects of fixation versus nonfixation of USF on DRF, or large prospective cohort studies assessing DRF with and without USF, with a minimum of 12 months follow-up.Level of Evidence Level II—therapeutic.
Keywords: radius; fracture; ulnar styloid; DRUJ stability